Transforming the agrifood processing sector in Africa: The role of industrial clusters - Tabiri, Kwasi Gyabaa; Sakyi, Daniel (AKADEMIYA2063, 2022)
Agriculture and the agrifood processing sector play an important role in many African economies. Agriculture accounted for approximately 53 percent of total employment in Africa south of the Sahara in 2019 while agricultural value added as a percentage of GDP stood at 17.2 percent in 2021 (World Bank 2022). The agrifood processing sector, which forms part of the wider agro-industrial sector,2 is also a key component in the manufacturing sector in many African economies (UNIDO 2012). For example, in Ghana, food manufacturing accounted for more than 33 percent of manufacturing value added in 2015. Moreover, food manufacturing’s share of total manufacturing stood at 14 percent in Egypt in 2018, and 58 percent in Zimbabwe in 2017 (UNIDO INDSTAT 2021). This underscores the fact that although the contribution of agrifood processing to total manufacturing may vary across countries, it remains a significant contributor to many African economies, and to meeting the food security needs of the population.